Persepsi Wali Murid Terhadap Pendidikan Anak Usia Dini di Desa Pandean. - Agus Sriyanto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2021)
by having knowledge of education, parents may not be able to provide education to their children, especially formal education. Early childhood education is a formal educational institution that is not obligatory for a child to enter primary school. The parents / guardians of underprivileged students in Pandean Village certainly have their own perceptions about this. With their economic conditions that are not yet prosperous, they continue to send their children to early childhood education institutions. This research uses descriptive qualitative research to describe the situations and events that have taken place. The research location is Pandean-Ngawi Village, the object of research on the perceptions of underprivileged students' parents / guardians, using the purposive sampling method and the Alo Liliweri analysis technique. Which cover; Stimulation, Organitation, Interpretation & Evaluation, Memory, and Recall. Based on the research results it can be concluded; 1) Early childhood education for underprivileged people is very important, the existence of early childhood education institutions is a special attraction for the wider community, including underprivileged people. 2) The experience of underprivileged students' parents / guardians of enrolling their children in PAUD institutions is different from the experiences of parents / guardians of students who are economically well-off. The parents / guardians of underprivileged students feel happy and proud because they can send their children to PAUD. An educational institution that is not a requirement for basic education. Economic constraints that resulted in late payment of tuition fees and not being able to give their child's pocket money became a very valuable experience for the parents / guardians of underprivileged students in Pandean-Ngawi Village